Deciphering the Role of Insulin-Like Growth Factor-I Receptor in Trastuzumab Resistance. (9th July 2012) - Nahta, Rita
Abstract : Resistance to the HER2-targeted antibody trastuzumab is a major clinical concern in the treatment of HER2-overexpressing metastatic breast cancer. Increased expression or signaling of the insulin-like growth factor-I receptor (IGF-IR) has been reported in a subset of cell lines and clinical samples derived from trastuzumab-resistant breast cancers. Genetic and pharmacologic inhibition of IGF-IR signaling has been shown to improve response to trastuzumab in trastuzumab-naïve and trastuzumab-resistant models. In this paper, we will discuss the role of IGF-IR signaling in trastuzumab resistance. Further, we will discuss cotargeting IGF-IR and HER2 as a potential therapeutic strategy for HER2-over-expressing breast cancers that have progressed on trastuzumab treatment.